Women’s Stories on the “Working of Talents” as Agents of Economic Transformation in South Africa - Tsara, Lindah; Mudau, Ndidzulafhi; Mudimeli, Lufuluvhi (Studia historiae ecclesiasticae, 2025)
In South Africa, the Forward in Faith International Ministries (FIFIM) is well known for educating its members on how to use their hands to raise their standard of living through the “working of talents.” Based on the “Matarenda Model of Entrepreneurship” described by Anderson (2018) and sometimes referred to as the “School of Talents” according to Guti (2015), this investigation uses qualitative analysis to gather information through secondary sources and oral history interviews. The study employs purposive sampling to identify participants and examine the importance of the “working of talents” in church and society through women’s experiences. It concludes that women can improve their living standards by utilising their abilities. The study strongly recommends that women in talent work should not limit themselves to achieving church goals only. They should continue to work diligently and utilise their gifts to recognise and seize opportunities that come their way, thus empowering themselves to achieve tremendous success. This study emphasises the crucial role of women in supporting churches and society in achieving Sustainable Development Goals (SDG) 5 and 8, which aim to alleviate poverty, empower women, and motivate them to continue their work.